Plasma diagnostics - Ovsyannikov, A. A.; Zhukov, M. F. (Mikhail Fedorovich) (Cambridge International Science Pub., 2000)
The book contains the results of investigations of electro-physical, chemical, gas-dynamic and other processes in low-temperature plasma and their diagnostics. Both conventional spectral and optical methods of diagnostics and new and laser methods are examined, together with electrostatic probes for investigating rarefied and dense plasma, especially in the presence of chemical reactions. Problems of probe calorimetry of plasma flows are investigated and approaches to measuring the spatial and time characteristics of plasma outlined. Procedural problems of processing experimental data and auto.